Per- and polyfluoroalkyl substances and fluorinated alternatives in urine and serum by on-line solid phase extraction–liquid chromatography–tandem mass spectrometry - Kato, Kayoko; Kalathil, Akil A.; Patel, Ayesha M.; Ye, Xiaoyun; Calafat, Antonia M. (Chemosphere (Oxford), 2018)
Per- and polyfluoroalkyl substances (PFAS), man-made chemicals with variable length carbon chains containing the perfluoroalkyl moiety (CnF2n+1–), are used in many commercial applications. Since 1999–2000, several long-chain PFAS, including perfluorooctane sulfonate (PFOS) and perfluorooctanoate (PFOA), have been detected at trace levels in the blood of most participants of the National Health and Nutrition Examination Survey (NHANES)—representative samples of the U.S. general population—while short-chain PFAS have not. Lower detection frequencies and concentration ranges may reflect lower exposure to short-chain PFAS than to PFOS or PFOA or that, in humans, short-chain PFAS efficiently eliminate in urine. We developed on-line solid phase extraction–HPLC–isotope dilution–MS/MS methods for the quantification in 50 μL of urine or serum of 15 C3-C11 PFAS (C3 only in urine), and three fluorinated alternatives used as PFOA or PFOS replacements: GenX (ammonium salt of 2,3,3,3,-tetrafluoro-2-(1,1,2,2,3,3,3-heptafluoropropoxy)-propanoate, also known as HFPO-DA), ADONA (ammonium salt of 4,8-dioxa-3H-perfluorononanoate), and 9Cl-PF3ONS (9-chlorohexadecafluoro-3-oxanonane-1-sulfonate), main component of F53-B. Limit of detection for all analytes was 0.1 ng/mL. To validate the method, we analyzed 50 commercial urine/serum paired samples collected in 2016 from U.S. volunteers with no known exposure to the chemicals. In serum, detection frequency and concentration patterns agreed well with those from NHANES. By contrast, except for perfluorobutanoate, we did not detect long-chain or short-chain PFAS in urine. Also, we did not detect fluorinated alternatives in either urine or serum. Together, these results suggest limited exposure to both short-chain PFAS and select fluorinated alternatives in this convenience population. •First mass-spectrometry method to quantify GenX, ADONA, and PFAS in urine or serum.•Serum is preferred to assess background exposure to long-chain PFAS for biomonitoring.•Biomonitoring of urine is preferred to assess background exposure to short-chain PFAS.